Integrated Policy Strategies for Addressing Out-of-School Children (OSC) in Metro City - Yuli Yanto (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2026)
Education is a fundamental right; however, Metro City faces an anomaly where 526 children remain out of school (ATS) despite achieving a